Status of Chronic Kidney Disease Patients Registered in National Kidney Center, Banasthali, Kathmandu - Mishra, D; Koirala, P (Journal of Manmohan Memorial Institute of Health Sciences, 2015)
Chronic kidney disease is a worldwide public health problem. In Nepal, Chronic kidney disease patients are increasing and the management of this disease is very expensive compared to other chronic diseases? We assessed the socioeconomic status of chronic kidney disease patients registered in National Kidney Centre, Banasthali, Kathmandu. The study used descriptive cross sectional design. Ninety six samples were collected between 15- 31 October, 2012.The mean age of the patients was 47 years, with almost half of the patients (46%) from 41-60 years age group. Among the patients, 65 % were male, 85% were married, 80% were literate, 57% were past smoker and 75% were drinker and 59% were from Kathmandu valley. Likewise, most of them were Newar, work as housewife as the main occupation. One third (37%) had to sell their property for the treatment. On an average patient spent Rs.240000 per year in dialysis. Similarly, medication cost was Rs.180000 and transplantation cost was Rs.500000 to 1000000. Preventive measures of the disease and subsidy in the treatment will be beneficial for the needy people. DOI: http://dx.doi.org/10.3126/jmmihs.v1i4.11997 Journal of Manmohan Memorial Institute of Health Sciences Vol. 1, Issue 4, 2015 Page : 19-23